Therapeutics for sickle cell disease intravascular hemolysis - Xue, Jianyao; Li, Xiang-An (Frontiers in Physiology, 2024)
Sickle cell disease (SCD) is a genetic disorder predominantly affecting individuals of African descent, with a significant global health burden. SCD is characterized by intravascular hemolysis, driven by the polymerization of mutated hemoglobin within red blood cells (RBCs), leading to vascular inflammation, organ damage, and heme toxicity. Clinical manifestations include acute pain crises, hemolytic anemia, and multi-organ dysfunction, imposing substantial morbidity and mortality challenges.Current therapeutic strategies mitigate these complications by increasing the concentration of RBCs with normal hemoglobin via transfusion, inducing fetal hemoglobin, restoring nitric oxide signaling, inhibiting platelet-endothelium interaction, and stabilizing hemoglobin in its oxygenated state. While hydroxyurea and gene therapies show promise, each faces distinct challenges. Hydroxyurea's efficacy varies among patients, and gene therapies, though effective, are limited by issues of accessibility and affordability. An emerging frontier in SCD management involves harnessing endogenous clearance mechanisms for hemolysis products. A recent work by Heggland et al. showed that CD-36-like proteins mediate heme absorption in hematophagous ectoparasite, a type of parasite that feeds on the blood of its host. This discovery underscores the need for further investigation into scavenger receptors (e.g. CD36, SR-BI, SR-BII) for their possible role in heme uptake and detoxification in mammalian species. In this review, we discussed current SCD therapeutics and the specific stages of pathophysiology they target. We identified the limitations of existing treatments and explored potential future developments for novel SCD therapies. Novel therapeutic targets, including heme scavenging pathways, hold the potential for improving outcomes and reducing the global burden of SCD.